2008
DOI: 10.1073/pnas.0711573105
|View full text |Cite|
|
Sign up to set email alerts
|

Kinetic analysis of a complete poxvirus transcriptome reveals an immediate-early class of genes

Abstract: Vaccinia virus is the prototypic orthopoxvirus and was the vaccine used to eradicate smallpox, yet the expression profiles of many of its genes remain unknown. Using a genome tiling array approach, we simultaneously measured the expression levels of all 223 annotated vaccinia virus genes during infection and determined their kinetics. Almost all of the genes were transcribed, and for 62 of these, this is the first empirical evidence of expression. Most remarkably, classification of the genes by their expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
168
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(187 citation statements)
references
References 43 publications
19
168
0
Order By: Relevance
“…Two categories of VACV early genes have been defined based on their temporal expression (Assarsson et al, 2008;Yang et al, 2010); their promoter motif (consensus sequence) and their promoter spacers were also recently reported (Yang et al, 2011a). To define the role of the promoter spacer in the optimization of early antigen expression, we designed two new promoters, LEO99 and LEO160, with distinct spacer lengths and compared them with the previously reported LEO (termed here LEO38) promoter .…”
Section: Discussionmentioning
confidence: 99%
“…Two categories of VACV early genes have been defined based on their temporal expression (Assarsson et al, 2008;Yang et al, 2010); their promoter motif (consensus sequence) and their promoter spacers were also recently reported (Yang et al, 2011a). To define the role of the promoter spacer in the optimization of early antigen expression, we designed two new promoters, LEO99 and LEO160, with distinct spacer lengths and compared them with the previously reported LEO (termed here LEO38) promoter .…”
Section: Discussionmentioning
confidence: 99%
“…Nine proteins from which HLA ligands were derived are among the 29 previously described immunogenic early proteins (10), and 4 proteins, B19R, E5R, G5.5R, and B15R, were newly identified in this study to contain relevant human CTL epitopes (Table VI). The proteins bearing HLA ligands functionally belong to two groups: proteins with immunomodulatory or host range and virulence function (B8R, B15R, B19R, C7L, and F12L (51,56,57)), and proteins functionally connected to DNA replication or transcription (E5R, A48R, G5.5R, A23R, D12L, and J6R (51)). The function of O1L is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising, because it had been shown for cells other than DC that proteins with late temporal expression can already be detected 4 h after infection, 6.5 h earlier than the time point at which the infected B-LCL were harvested for HLA ligand purification (43,51). Therefore, we analyzed the levels of viral protein expression and viral HLA ligand presentation in infected B-LCL simultaneously.…”
Section: Comparison Between the Levels Of Viral Protein Expression Anmentioning
confidence: 99%
“…S3), as has been done previously for transcriptional clustering (14,15). These studies showed that, in general, genes with products that are involved in DNA replication and host interaction are expressed at earlier times, followed by those involved in transcription, with virion components only expressed at later times.…”
Section: Discussionmentioning
confidence: 88%
“…A separation of early genes into two classes by a cluster analysis of the VACV transcriptome was done first by Assarsson et al by tiling microarray and then Yang et al using deep sequencing of poly(A) RNA (14,15). However, these descriptive data remain unsupported by the current understanding of VACV transcriptional control and more recent studies focus on the three known classes of promoter (early, intermediate and late) and the consequences of these elements being combined (16,37).…”
Section: Discussionmentioning
confidence: 99%